Induction of defense related enzymes and phenols in chilli plants by Bacillus subtilis against anthracnose pathogen, Colletotrichum capsici - and R. RANGESHWARAN, B. RAMANUJAM*, HONNUR BASHA, VINAYA HEMANNAVAR, P. CHOWDAPPA (Indian Phytopathology, 2012)
Bacillus subtilis (EXB-123, ENB-24 and S-9) isolates were identified as potential bacterial antagonists against chilli anthracnose pathogen, Colletotrichum capsici based on fruit bioassay studies. These isolates were screened for their ability to induce defense related enzymes like peroxidase (PO), polyphenoloxidase (PPO), phenylalanine ammonia-lyase (PAL) and total phenols against C. capsici in chilli plants of Byadagi dabbi variety. Chilli plants treated with bacterial antagonist along with C. capsici showed higher levels of defense related enzymes and phenols compared to antagonist alone and untreated plants. Among the three bacterial antagonists tested, B. subtilis EXB-123 showed the higher activities of total phenols (66.03 Î¼g g-1 compared to control 34.56), PO (3.53 change in OD min-1g-1 compared to control 0.52), PAL (1040 nmol trans cinnamic acid min-1g-1 compared to control 390nmol) and PPO activity (0.04 change in OD min-1g-1 compared to control 0.01) in chilli plants treated with C. capsici. Native PAGE analysis of enzyme extracts of chilli plants treated with B. subtilis EXB-123 and C. capsici showed multiple isoforms indicating the higher induction of PO and PPO. The other two isolates, ENB-24 and S-9 showed similar trend but the enzyme activities and phenol content were less compared to EXB-123. The present study has helped in identifying an isolate of B. subtilis, EXB-123 with higher ability to induce defense related compounds in chilli plants against C. capsici.